The Effects of Parenteral K1 Administration in Pseudoxanthoma Elasticum Patients Versus Controls. A Pilot Study - Carrillo-Linares, Juan Luis; García-Fernández, María Inmaculada; Morillo, María José; Sánchez, Purificación; Rioja, José; Barón, Francisco Javier; Ariza, María José; Harrington, Dominic J.; Card, David; Boraldi, Federica; Quaglino, Daniela; Valdivielso, Pedro (Frontiers in Medicine, 2018)
Introduction Pseudoxanthoma elasticum (PXE) is a rare disease caused by mutations in the ABCC6 gene. Vitamin K1 is involved in the post-translational carboxylation of some proteins related to inhibition calcification process. Our aim was to investigate whether parenteral administration of vitamin K1 is effective in modulating the levels of circulating vitamin-K-dependent proteins and metabolites in patients affected by Pseudoxanthoma elasticum.